An evaluation of the global health security agenda steering group governance interventions. (30th September 2020) - DeShore, N E; Johnson, J A; Malone, P; Greenhill, R; Wuenstal, W
Abstract: Background: Member States lack of compliance with 2005 IHR implementation led to the launched of the Global Health Security Agenda. This research will provide an understanding of how the Global Health Security Agenda Steering Group (GHSA SG) governance interventions impact health system performance and global health security. This will enhance the understanding of a Steering Group's governance interventions in complex Global Health initiatives. Research questions: To what extent have GHSA SG governance interventions contributed towards enabling health system performance of WHO Member States? To what extent have GHSA SG governance interventions contributed towards the implementation of global health security among WHO Member States? Methods: Correlational analysis using Spearman's rho examined the relationship between governance, health system performance and global health security variables at one point in time. A convenience non-probability sample consisting of eight WHO Member States was used. SPSS Statistics generated the bivariate correlation analyzes. Results: Governance and health system performance analysis indicated a statistically significant strong positive effect size in 11 out of 18 and moderate positive effect size in the remaining seven out of 18 health system performance indicators. Governance and global health security analysis concluded three of the governance indicators had strong and moderate positive coefficients. Global health security variables demonstrated weak effects in the remaining three governance indicators. Conclusions: This study presents a case for health systems embedding in global health security. Health system performance is only as effective at protecting populations when countries achieve core capacities of preparedness and response to global health threats. The associations provide stakeholders information about key characteristics of governance that influence health system performance and global health security implementation. Key messages: This study provides an argument for the continued support of the GHSA 2024 Framework with implementation of global health security capabilities and meeting 2005 IHR requirements. The GHSA SG governance role remains profoundly important in establishing sustainable efforts internationally towards achieving the objectives of the GHSA in support of the 2005 IHR standards.